The Role of the IL-33/ST2 Axis in CpG-Induced Macrophage Activation Syndrome - Yuanji Dong; Rongfen Gao; Kailin He; Jixin Zhong; Lingli Dong (Journal of Immunology Research, 2023)
Background. Macrophage activation syndrome (MAS) is a fatal inflammatory condition, which is often associated with the elevation of multiple proinflammatory cytokines and multiple organ dysfunction. Previous studies have shown that ST2 contributes to T cell overactivation and plays a detrimental role in mouse models of primary hemophagocytic lymphohistiocytosis. The purpose of this study was to investigate the role of the IL-33/ST2 axis in a mouse model of MAS induced by repeated injections of cytosine–phosphate–guanine (CpG). Methods. Serum cytokines were determined using the cytometric bead array by flow cytometry. IL-33 and ST2 were detected by immunohistochemistry and real-time quantitative PCR in the liver and spleen of mice. CD3 and F4/80 in the liver were detected by immunohistochemistry. Inflammatory macrophages and effector memory T lymphocytes were detected by flow cytometry. Result. The CpG-induced MAS model was successfully induced after repeated CpG injections, presenting with hypercytokinemia and hepatosplenomegaly. The numbers of IL-33 positive cells in the liver and spleen decreased significantly, while the expression of ST2 in the liver tended to increase in the mice with MAS. IL-33 and St2 knockout mice showed similar levels of hepatosplenomegaly, peripheral blood count, and cytokine storm when compared with wild-type (WT) mice after induction of MAS. There were also no significant differences in liver pathology (including inflammatory cell infiltration of CD3 and F4/80) and levels of splenic inflammatory macrophages and effector memory T cells between the WT and knockout mice. Conclusion. These results suggested that IL-33 decreased in the liver and spleen tissues of MAS mice. Further results suggest that IL-33 and St2 knockout mice have no treatment potential in CpG-induced MAS. Thus, the IL-33/ST2 axis has little effect on the prognosis of CpG-induced MAS.